2007
DOI: 10.1210/en.2006-1313
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines and the Regulation of Lipid Metabolism in Growth Hormone Transgenic and Calorie-Restricted Mice

Abstract: Chronic elevation of GH induces resistance to insulin and hyperinsulinemia in both humans and animals, whereas calorie restriction (CR) improves peripheral insulin sensitivity in many species. To investigate the mechanisms that lead to insulin resistance in animals with high levels of GH as well as the mechanisms that might improve insulin sensitivity, we fed GH-overexpressing transgenic mice ad libitum or subjected them to 30% CR. We then assayed the plasma adipocytokines levels related to insulin sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 50 publications
(43 reference statements)
6
96
0
4
Order By: Relevance
“…FA synthesis, clearance, and release are regulated by neuroendocrine factors including GH, whose levels vary under conditions of changing energy supply (2). Recent animal studies have underscored the important role of hepatic GH signaling in the development of NAFLD and the metabolic syndrome (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…FA synthesis, clearance, and release are regulated by neuroendocrine factors including GH, whose levels vary under conditions of changing energy supply (2). Recent animal studies have underscored the important role of hepatic GH signaling in the development of NAFLD and the metabolic syndrome (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…However, 16-months' CR does not significantly increase the plasma concentration or the mRNA level of Adipoq in the epididymal fat tissue (Wang, 2006). A 25% CR regimen using a diet formulated to be isocaloric with the control diet (American Institute Nutrition (AIN)-93M diet) with 25% increases in protein, vitamin, mineral and fat content did not elevate the plasma Adipoq concentration in mice of a mammary tumor model during a 64-week-long experiment (Dogan, 2010).…”
Section: Gene Expression In Wat Associated With Energy Metabolismmentioning
confidence: 91%
“…GH treatment promotes a state of intrahepatic triglyceride storage. Several studies in bGHtransgenic mice, defficient GHR-JAK2-STAT-5 signaling pathway, GH-treated intact or GHdeficient rats (hypophysectomized or hypothyroid), as well as experiments in PPAR null mice, have all revealed that GH down-regulates genes involved in lipid oxidation and increases the expression of genes promoting lipogenesis in the liver (Olsson et al, 2003;Wang et al, 2007;Barclay et al, 2011;Sos et al, 2011). On the other hand, an impaired GHR-JAK2-STAT-5 signaling strongly correlates with hepatic steatosis (Fan et al, 2009;Barclay et al, 2011;Sos et al, 2011).…”
Section: Gh and Metabolismmentioning
confidence: 99%